Lifecycle, culture, and maintenance of the emerging cephalopod models Euprymna berryi and Euprymna morsei - Jolly, Jeffrey; Hasegawa, Yuko; Sugimoto, Chikatoshi; Zhang, Lin; Kawaura, Risa; Sanchez, Gustavo; Gavriouchkina, Daria; Marlétaz, Ferdinand; Rokhsar, Daniel (Frontiers in Marine Science, 2022)
Cephalopod research remains limited by the inability to culture species under laboratory conditions for multiple generations to provide continuous access to animals at all stages of the life cycle. Here, we describe a multi-generational laboratory culture system for two emerging cephalopod models: the hummingbird or Berry’s bobtail squid, Euprymna berryi Sasaki, 1929, and Morse’s bobtail squid, Euprymna morsei Verrill, 1881, which are primarily found off mainland Japan. E. berryi wild adults were spawned and raised to the third filial generation, and E. morsei wild adults were spawned and raised to the second filial generation in a closed system at 20°C. We report growth and survivorship data for a cohort of 30 individuals across the first generation raised in captivity. E. berryi and E. morsei grew exponentially during the first 90 and 60 days post-hatching, respectively. Survivorship at the first spawning event for E. berryi and E. morsei was 90% and 77%. E. berryi and E. morsei females spawned after days 112 and 71 days post-hatching, respectively. We describe the life history of each species and how to distinguish sexes. We discuss the challenges of cephalopod culture and how culturing these species address those problems.